Family Experiences and Feedback: An Examination of Attrition in Parent-Child Interaction Therapy. Issue 1 (2nd January 2023) - Liebsack, Brittany K.; Herschell, Amy D.; Hart, Jonathan A.; Kolko, David J.; Jackson, Carrie B.
ABSTRACT: Attrition is a significant problem in child psychotherapyand has serious implications for overall treatment effectiveness. Predictors of attrition include those at the client, therapist, and treatment levels. The current study investigated factors associated with attrition in Parent-Child Interaction Therapy (PCIT), an evidence-based parent training program for families with young children with disruptive behavior disorders. The sample of 67 caregivers were treated by 25 therapists from 19 different licensed psychiatric outpatient clinics across one state and were part of a larger study (RO1 MH09750; PI: Herschell). The effects of caregivers' attitudes toward therapy, expectations of therapy, perceived therapist cultural competence, and commitment to treatment were examined using Binomial Logistic Regression. Therapy expectations and commitment to treatment added significantly to the model predicting attrition. Fleiss' kappa was used to examine caregiver-therapist agreement on completion status, reasons PCIT ended, barriers to treatment experienced by families, and caregiver compliance with post-treatment therapist referrals. Results suggest low agreement across each variable, indicating that therapists may not be aware of caregiver barriers or reasons they leave PCIT prematurely. Limitations, suggestions for future research, and clinical implications are discussed.